PENGARUH UKURAN KANTOR AKUNTAN PUBLIK, SPESIALISASI INDUSTRI AUDITOR DAN AUDIT TENURE PADA BIAYA MODAL EKUITAS ( Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2010 – 2012) - Desiliani, Nabella; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the relation between audit quality to the cost of equity capital. Variables tested in this study, namely the cost of equity capital is proxied using the earning price ratio, the size of the public accounting firm, auditor industry specialization and audit tenure. The population in this study consists of all listed firm in Indonesia Stock Exchange in year 2010, 2011, and 2012. Sampling method used is purposive sampling. A total of 66 companies in Indonesia that meet the criteria that have complete data for this study, which is expressed as a sample. This study uses multiple regression as the analysis technique using SPSS. Test results of this study indicate that the size of the audit firm is negatively significant related to the cost of equity capital. Auditor industry specialization are positively significant related to the cost of equity capital. While the audit tenure negatively related and does not significantly affect the cost of equity capital.